Causes and Forms of Exploitation of Street Children During the Covid-19 Pandemic In Makassar City - Seknun, Amina; Yusriani, Yusriani; Muchlis, Nurmiati (Jurnal EduHealth, 2022)
The research was conducted to determine the causes and forms of exploitation of street children during the COVID-19 pandemic in the city of Makassar. This research is a quantitative research, analytical descriptive. The population is street children in the city of Makassar with a sample of 135 respondents. Methods of data collection is done by using a questionnaire. Furthermore, editing, coding, entry, cleaning, and tabulating data are carried out. Then the data is processed using a computer. The results of the study indicate that the factors that are indicated to trigger are economic conditions, loss of parents, family harmony, lifestyle of the surrounding environment, and economic motivation. The type of work that is mostly done by street children is being a beggar and selling tissue, each of which is 72.6%. Based on the percentage, it can also be described that more than 60% of respondents have multiple jobs. This condition indicates that street children who are respondents experience high work exploitation because they do two or more jobs. The conclusion that causes the exploitation of street children that deserve attention is related to economic conditions, loss of parents, family harmony, lifestyle of the surrounding environment, and economic motivation. It is necessary to map the potential of street children and be integrated through social rehabilitation programs so that the potential of street children can be channeled and contribute to improving welfare.